Disputed State, Contested Hospitality: Dutch Ambassadors in Search of a New Overlord at the French Court of King Henry III, 1584-1585 - van Leuveren, Bram (Early Modern Low Countries, 2020)
In December 1584, the States-General of the Union of Utrecht dispatched a special embassy to Paris to offer King Henry III of France the titular rule of their estates. Henry was to replace Philip II of Spain, the legitimate overlord of the seventeen provinces, whom the States-General had deposed in July 1581 in direct violation of the sacred institution of the monarchy. Although largely overlooked by historians, the special embassy provides a fascinating insight into the intricate European ramifications of the Union of Utrecht’s search for overlordship prior to the foundation of the Dutch Republic in April 1588. This article focuses on the divided reception of the special embassy to France from the perspective of the Union of Utrecht, especially among the powerful nobility of Holland, many of whom shared anti-French sentiments, and from the vantage point of the English and Spanish ambassadors in Paris, who tried to either intervene or obstruct the Dutch-French negotiations in a bid to alter Europe’s balance of power to their advantage. By bringing together dispatches and the reported reactions of Dutch, English, and Spanish emissaries that have not been studied in detail before, and never alongside each other, this article argues that Henry III’s calculated and pragmatic use of diplomatic ceremony played a defining role in managing the fraught relations between France and the Union of Utrecht, Spain, England, and the other Catholic powers at the French court.